Education for critical consciousness - Freire, Paulo (London ; New York : Continuum, 2005)
Paulo Freire (1921-97) was an educationalist based in Brazil who became the most influential writer and thinker on education in the second half of the twentieth century. His seminal work Pedagogy of the Oppressed has sold a million copies." "Education for Critical Consciousness is the main statement of Freire's revolutionary method of education. It takes the life situation of the learner as its starting point and the raising of consciousness and the overcoming of obstacles as its goals. For Freire, man's striving for his own humanity requires the changing of structures which dehumanise both the oppressor and the oppressed.
Includes bibliographical references.
Keywords: Educational sociology -- Latin America; Critical pedagogy